Penggunaan Terapi Komplementer Terkait Kualitas Hidup Survivor Kanker Payudara Stadium Lanjut - Stevani Basry; Kusman Ibrahim; Ida Maryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to see how the effect of complementary therapy on the quality of life of survivors of advanced breast cancer. The research method used is a scoping review where the author uses four databases, namely Google Scholar, Pubmed, Proquest, and Science direct, from 2013 to 2021. The type of research sought uses cross-sectional and retrospective observational. The results showed that alternative, complementary therapies often used by breast cancer survivors were herbs, spiritual therapy, vitamin and mineral supplements, mind-body manipulative practices, and exercise. However, five articles state that there is no association between the use of CAM on the quality of life of breast cancer survivors. However, seven other articles said that there was a positive effect of CAM on the quality of life of breast cancer survivors. In conclusion, the coordination of alternative, complementary medicine with conventional cancer treatment and standard procedures will ensure that patient care can be provided with maximum quality standards, the highest information standards, and maximum treatment safety. Keywords: Breast Cancer, Quality of Life, Complementary and Alternative Medicine